Development of distributed consensus protocol for multi-unmanned aerial vehicle coordination - Tan, Seet Ynn (Nanyang Technological University, 2022)
Advancements in robotics and control theory have equipped robots to communicate with one another and process data more quickly. Robot-to-robot communication enables multi-robot coordination. An abundance of benefits associated with multi-robot coordination includes increased overall performance, increased robustness, and completing complex tasks impossible for single robots. Current solutions often decompose the problem of multi-robot coordination into the problem of robot task allocation. These apply market-based distributed bidding models to allocate tasks. However, these market-based solutions do not necessarily provide guarantees of consistency, partition tolerance, and global ordering of operations. It is crucial to provide these guarantees to ensure that the individual views of the overall state of the robot swarm are the same across all robots. Failing to agree on a shared decision can cause significant ramifications, like system failures and threats to human life. Distributed consensus protocols, like Raft, provide these guarantees. Raft guarantees strong consistency with partition tolerance for system models with partial synchroneity, crash-recovery behaviour of nodes, and fair-loss links.